EXPERT SYSTEM IDENTIFICATION OF A PERSONALITY GRADE XI AGRIBUSINESS AGRICULTURAL TECHNOLOGY AT SMK NEGERI 6 TAKALAR - Taha, Syamsumarlin; Syarif, Irwan (Department of Electrical Engineering, University of Patria Artha, 2017)
This research aims to develop a software expert system regarding the identification of personality of students. This research is research Research & Development (R&D). In building this system used the programming language Visual Basic 6.0 and Microsoft Access as a data storage.Â The results of this research is a system that makes it easy for a person to identify his/her personality. The system test is performed using the method writer black box with the results of the functions in the system has been functioning properly. Then conducted trials to the user and the results of the response that is the use of an expert system is very easy to use.Â Â